Measuring systemic funding liquidity risk in the Russian banking system - Irina Andrievskaya (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
The 2007-2009 global financial crisis demonstrated the need for effective systemic risk measurement and regulation. This paper proposes a straightforward approach for estimat-ing the systemic funding liquidity risk in a banking system and identifying systemically critical banks. Focusing on the surplus of highly liquid assets above due payments, we find systemic funding liquidity risk can be expressed as the distance of the aggregate liquidity surplus from its current level to its critical value. Calculations are performed using simu-lated distribution of the aggregate liquidity surplus determined using Independent Compo-nent Analysis. The systemic importance of banks is then assessed based on their contribu-tion to variation of the liquidity surplus in the system. We apply this methodology to the case of Russia, an emerging economy, to identify the current level of systemic funding li-quidity risk and rank banks based on their systemic relevance.
URN:NBN:fi:bof-201408072117
Keywords: G21; G28; P29; 330; systemic risk; liquidity surplus; banking; Russia